2020
DOI: 10.1093/gastro/goaa085
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate protects against lipopolysaccharide-induced liver injury partially via the GPR43/ β-arrestin-2/NF-κB network

Abstract: Background Butyrate acts as a regulator in multiple inflammatory organ injuries. However, the role of butyrate in acute liver injury has not yet been fully explored. In the present study, we aimed to investigate the association between butyrate and lipopolysaccharide (LPS)-induced acute liver injury and the signaling pathways involved. Methods LPS-induced acute liver injury was induced by intraperitoneal injection of LPS (5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…It has been demonstrated that the uptake of butyrate and its synthetic derivative, N-(1-carbamoyl-2-phenyl-ethyl) butyramide (FBA), in the liver can enhance fatty acid oxidation by activating AMPK-acetyl-CoA carboxylase against fatty liver ( 84 ). In addition, butyrate exerts protective effects by activating the GPR43/β-arrestin-2/NF-κB network against LPS-induced liver injury in a mouse model ( 85 ).…”
Section: Potential Mechanisms Of Resistant Starches On Regulating The...mentioning
confidence: 99%
“…It has been demonstrated that the uptake of butyrate and its synthetic derivative, N-(1-carbamoyl-2-phenyl-ethyl) butyramide (FBA), in the liver can enhance fatty acid oxidation by activating AMPK-acetyl-CoA carboxylase against fatty liver ( 84 ). In addition, butyrate exerts protective effects by activating the GPR43/β-arrestin-2/NF-κB network against LPS-induced liver injury in a mouse model ( 85 ).…”
Section: Potential Mechanisms Of Resistant Starches On Regulating The...mentioning
confidence: 99%
“…LPS, a main component of outer cell membrane of Gram-negative bacteria, has been recognized as one of the most potent microbial initiators of inflammation (Li et al, 2019;Ko et al, 2019). Upon stimulation with LPS, RAW 264.7 macrophages cells could trigger the secretion of numerous inflammatory cytokines and mediators such as NO, TNF-α, IL-6 and so on (Luo et al, 2020). NO is a vital cellular signaling and defensing molecule involved in inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…SCFA also activate GPR109A to stimulate the production of IL-18, promoting intestinal homeostasis and preventing colitis [ 50 ]. GPR43-deficient mice showed increased sensitivity to dextran sodium sulfate-induced colitis [ 51 ]. In recent studies, SCFA have been shown not only to exert its anti-inflammatory and protective properties in the intestines but also to reach the circulatory system, directly affecting the adipose tissue, brain, and liver and producing beneficial metabolic effects [ 52 ].…”
Section: Intestinal Flora and Its Metabolitesmentioning
confidence: 99%